The boy in the striped pyjamas - Trewin, Anna (Penguin readers. Level 4, 2020)
Berlin, 1942: When Bruno returns home from school one day, he discovers that his belongings are being packed in crates. His father has received a promotion and the family must move to a new house far, far away, where there is no one to play with and nothing to do. A tall fence stretches as far as the eye can see and cuts him off from the strange people in the distance. But Bruno longs to be an explorer and decides that there must be more to this desolate new place than meets the eye. While exploring his new environment, he meets another boy whose life and circumstances are very different from his own, and their meeting results in a friendship that has devastating consequences.